Phrase Position, but not Lexical Status, Affects the Prosody of Noun/Verb Homophones - Conwell, Erin; Barta, Kellam (Frontiers in Psychology, 2018)
Words that can occur in more than one lexical category produce regions of ambiguity that could confound language learning and processing. However, previous findings suggest that pronunciation of noun/verb homophones may, in fact, differ as a function of category of use, potentially mitigating that ambiguity. Whether these differences are part of the lexical representation of such words or mere by-products of sentence-level prosodic processes remains an open question, the answer to which is critical to resolving questions about the structure of the lexicon. In three studies, adult native speakers of English read aloud passages containing noun/verb homophones or nonce words used in both noun and verb contexts. Acoustic measurements of the target words indicated that, while sentence position influences the acoustic properties of noun/verb homophones, including duration and pitch, there are not significant effects of lexical category when other factors are controlled. Furthermore, the lexical status of a word (real or nonce) does not produce consistent prosodic effects. These findings suggest that previously reported prosodic differences in noun/verb homophones may result from the syntactic positions in which those categories tend to occur.